Intangible investments and innovation propensity: Evidence from the Innobarometer 2013. Issue 4 (18th May 2016) - Montresor, Sandro; Vezzani, Antonio
Abstract: This paper investigates the innovation impact of intangible investments. Drawing on the resource-based view of the firm, we argue that through intangible investments, companies acquire knowledge assets that increase their innovativeness. However, a greater innovation impact is expected from investing more in technological intangibles rather than in intangibles overall, and a greater one from using internal versus external resources. Through a new survey on a large sample of firms in 36 countries, accounting for different intangibles and addressing their endogeneity through proper instruments, these hypotheses are partially confirmed. Developing intangibles internally is actually the most innovation-impacting aspect, but not in manufacturing. Instead, by controlling for this choice and for that of investing in technological intangibles, the intensity of intangible resources is significant for innovation in manufacturing only. Policy/strategic implications about the need of readdressing the boost to intangible investments for the sake of innovation in Europe are drawn accordingly.